Evaluation of a hybrid system of renewable electricity generation for a remote area of Colombia using homer software - Muñoz, Yecid; Guerrero, Julian; Ospino, Adalberto (TECCIENCIA, 2014)
Subsequent to the study of the energy demand and the evaluation of possible available resources in the remote area of Riosucio, Chocó region, Colombia, an analysis is performed on the implementation of three alternative systems of power generation. The first is a micro hydroelectric power station on the Truando River, which includes the design using HOMER software simulation, the costs of building and implementation, and its share in the energy mix. The second system is an array of photovoltaic panels in isolated configuration. This will include the design, via HOMER software simulation, of batteries, panel distribution, inverters, and connections, for a usable specific area restricted by the limited solar resource of the area. Finally, wind power is analyzed, a system that will include the determination of the most suitable turbine for the available wind resource in the area, as well as the analysis of the ideal quantity of wind generators based on its share in the energy mix and associated costs. For each of the assessed systems, a financial analysis and the feasibility are obtained, based on the investment, percentage of energy, and the electricity savings for each of the homes.